Insoluble adsorption defluorination composite material particle as well as preparation method and application thereof and defluorination bag
By mixing calcium phosphate, ethyl cellulose and anhydrous ethanol in a certain proportion, the insoluble adsorption fluorine removal composite material particles are solved, and the problem of difficulty in separation of fluorine removal agents in the prior art is solved, and an efficient and safe brick tea fluorine reduction effect is achieved.
Patent Information
- Application Number
- CN202411451236.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-10-17
AI Technical Summary
In the prior art, fluorine-depleting agents are often used when reducing the fluorine content in brick tea, but these materials are difficult to separate from raw materials or tea soup, which may affect the fermentation process or damage the quality of brick tea, and pose a safety risk of using non-food raw materials.
The insoluble adsorption and fluorine removal composite particles prepared by mixing calcium phosphate, ethyl cellulose and anhydrous ethanol in a certain proportion. This material can be made into fluorine removal packages, which are used to directly remove fluorine in water or tea soup, and have little impact on the pH value of water or tea soup.
It has achieved effective reduction of the fluorine content in brick tea water without changing the production process and tea drinking habits, and the material is safe and easy to achieve, and the fluorine removal rate can reach more than 85%.
Smart Images

Figure CN119565571A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of adsorption defluorination, and specifically relates to insoluble adsorption defluorination composite material particles and a preparation method, application and defluorination bag thereof. Background Art
[0002] Brick tea has the effects of anti-oxidation, weight loss and lipid reduction, and gastrointestinal regulation. Fluorine is the main risk factor affecting the safety of brick tea drinking. Long-term drinking of brick tea with high fluoride content will increase the risk of "tea drinking type fluoride poisoning", which is mainly manifested as dental and bone lesions. Fluorine mainly accumulates in the leaves of tea trees, generally showing mature leaves > young leaves. Since brick tea is usually fermented and pressed from the coarse old branches and leaves of tea trees, the fluoride content is relatively high. Therefore, how to effectively reduce the fluoride content of green brick tea is a technical problem that needs to be solved urgently.
[0003] At present, the technology to reduce the fluoride content in brick tea is mostly to add defluoridation agents during the production process of brick tea. Patent CN99115669.2 uses pearl calcium or persimmon leaf powder or bone charcoal powder as a fluoride-reducing additive to develop low-fluoride brick tea. Patent CN02138955.1 discloses a method of adding defluoridation agent bone charcoal or hydroxyapatite or tricalcium phosphate to brick tea, and then boiling, filtering and drying to prepare low-fluoride brick tea powder. Patent CN200410081249.6 calcines serpentine at high temperature, then cools and crushes it into powder, and boils it with brick tea in a certain proportion to reduce the fluoride content of brick tea water. Patent CN200910058301.9 controls the fluoride content by adding iron salt solution during the tea making process. Patent CN 201910342534.5 produces low-fluoride brick tea by evenly spreading highland barley water extract on tea leaves and naturally fermenting at room temperature. Patent CN200710050384.8 achieves the preparation of low-fluoride brick tea by adding EM composite microbial preparations or GM microbial preparations during the fermentation process. Patent CN201410043191.X produces low-fluoride brick tea by adding a mixture of calcium citrate and calcium carbonate as a defluoridation agent to the brick tea raw materials. The above-mentioned defluoridation technology mainly adds fluoride removal materials when preparing brick tea. The materials are mostly powders and difficult to separate from the raw materials or tea soup. It is very likely to affect the fermentation of the raw materials or destroy the original quality of the brick tea. At the same time, there is a situation where non-food raw materials are used, and it is unknown whether new safety risks are introduced.
[0004] In addition, although calcium phosphate is a good fluoride removal material and can effectively remove fluoride ions in water or tea, its particle size is too small to be directly made into a fluoride removal bag to conveniently remove fluoride in water or tea. When calcium phosphate is directly added to the aqueous solution, it has a greater impact on the pH value of the water or tea. Summary of the invention
[0005] In order to solve the deficiencies of the prior art, the present invention provides an insoluble adsorption defluorination composite material particle and its preparation method, application and defluorination bag. The present invention is a composite material prepared by mixing calcium phosphate, ethyl cellulose and anhydrous ethanol in a certain proportion. It is a water-insoluble granular material and can be made into defluorination bags of various specifications. It can remove fluorine in water or tea soup very conveniently and quickly, has little effect on the pH value of water or tea soup, and the preparation method is simple and easy to implement.
[0006] The technical solution provided by the present invention is as follows:
[0007] A method for preparing insoluble adsorption and defluorination composite material particles comprises the following steps:
[0008] 1) dissolving ethyl cellulose in anhydrous ethanol to form a uniform colloid;
[0009] 2) adding calcium phosphate, a food additive, to the colloid obtained in step 1) while stirring to obtain a uniform mixed material;
[0010] 3) While the homogenizer is running at high speed, the mixed material obtained in step 2) is slowly added into water, and the ethyl cellulose forms a film when it meets water, and composite material particles are obtained by homogenization;
[0011] 4) placing the composite material particles obtained in step 3) on a 60-mesh sieve, washing with water, and sieving out composite material particles with a particle size of more than 60 mesh and uncompounded calcium phosphate powder;
[0012] 5) Collecting the cleaned sieve-surface composite material particles obtained in step 4) and drying them to obtain the insoluble adsorption and defluorination composite material particles.
[0013] The above technical solution prepares a composite material by mixing calcium phosphate, ethyl cellulose and anhydrous ethanol in a certain proportion. The composite material can be made into a defluorination bag.
[0014] The above technical solution is to dissolve ethyl cellulose in anhydrous ethanol, stir it thoroughly, obtain a colloid of ethyl cellulose and anhydrous ethanol, then add calcium phosphate, a food additive, to the colloid, stir it thoroughly, and mix it evenly. Then pour the mixed ethyl cellulose-anhydrous ethanol-calcium phosphate mixture into water, and homogenize it with a homogenizer while pouring; the product is sieved, washed, separated, and dried to obtain adsorption and defluorination composite materials of different specifications.
[0015] The adsorption and defluorination composite material prepared by the present invention is a water-insoluble granular material, the surface of which is rich in hydroxyl active groups, and the material properties are stable and safe. It can be made into defluorination bags, filter materials, filter elements, etc., and directly used for defluorination in tea soup and drinking water. At a usage amount of 40g / L, it can be used to remove fluoride from 5mg / L to 15mg / L water or tea soup within 30 minutes to reach the drinking water standard of less than 1mg / L, and the defluorination rate can reach more than 85%.
[0016] Specifically, in step 1), the weight ratio of ethyl cellulose to anhydrous ethanol is 6:100 to 18:100, preferably 18:100.
[0017] Specifically, in step 2), the weight ratio of ethyl cellulose to calcium phosphate is 18:10 to 18:100, preferably 18:50.
[0018] Specifically, in step 3), the homogenization speed is 8000-12000 rpm, preferably 10000 rpm.
[0019] Specifically, in step 5), the drying temperature is 100-110° C., preferably 105° C. The drying time is 4-6 hours.
[0020] The present invention also provides insoluble adsorption and defluorination composite material particles prepared according to the above preparation method.
[0021] Specifically, the particle size is 0.25 mm to 2 mm.
[0022] Specifically, its solubility is less than 0.01 g / 100 g.
[0023] Specifically, when the weight ratio of ethyl cellulose to calcium phosphate is 18:50, the fluorine adsorption capacity of the composite material particles is 4.90 mg / g (normal temperature) and 7.87 mg / g (95° C.).
[0024] The present invention also provides the application of insoluble adsorption defluorination composite material particles for preparing defluorination bags or defluorination agents.
[0025] The present invention also provides a defluorination bag, comprising a sealed bag and insoluble defluorination adsorption composite material particles filled in the bag.
[0026] The beneficial effects of the present invention are as follows:
[0027] Compared with the existing brick tea defluorination technology, the present invention uses all food-grade preparation raw materials, and achieves the purpose of effectively reducing the fluoride in brick tea water without changing the production process of brick tea and the traditional tea drinking habits;
[0028] In addition to being used for defluorination of brick tea and water, the defluorination material of the present invention can also be used as a new type of adsorption material for defluorination of tea products in deep processing, defluorination of drinking water, etc., and has a wide range of application prospects;
[0029] The technical solution of the present invention is easy to implement and simple to implement. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a scanning electron microscope image of the insoluble adsorption and defluorination composite material particles provided in Example 3. DETAILED DESCRIPTION
[0031] The principles and features of the present invention are described below. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.
[0032] Unless otherwise specified, the test methods used in the examples of the present invention are all conventional methods; the raw materials used are all commercially available unless otherwise specified.
[0033] Example 1
[0034] The preparation of insoluble adsorption and defluorination composite material particles comprises the following steps:
[0035] Step 1: Weigh ethyl cellulose and anhydrous ethanol in a weight ratio of 18:100, first pour all the anhydrous ethanol into a beaker (or similar container), then add ethyl cellulose into the beaker, stirring while adding to completely dissolve the ethyl cellulose (when the room temperature is low in winter, it can be heated slowly). Wait until the ethyl cellulose and anhydrous ethanol form a uniform colloid.
[0036] Step 2: Add 30 parts of food additive calcium phosphate to the system in step 1, stirring while adding until the entire system is completely mixed.
[0037] Step 3: Slowly add the mixed materials in the system of step 2 into a beaker filled with water (the amount of water is one-third to two-thirds of the capacity of the vessel), and homogenize with a high-performance homogenizer at a speed of 10,000 rpm. Ethyl cellulose forms a film when it comes into contact with water, and composite material particles are obtained by homogenization.
[0038] Step 4: Place the homogenized material in step 3 on a 60-mesh sieve, wash with water (which can be running water), and sieve out the composite material with a particle size above 60 mesh and the uncompounded calcium phosphate powder.
[0039] Step 5: Collect the cleaned composite material in step 4 and dry it in an oven at 105° C. for about 5 hours.
[0040] Example 2
[0041] The preparation of insoluble adsorption and defluorination composite material particles comprises the following steps:
[0042] Step 1: Weigh ethyl cellulose and anhydrous ethanol in a weight ratio of 18:100, first pour all the anhydrous ethanol into a beaker, then add ethyl cellulose into the beaker, stirring while adding to completely dissolve the ethyl cellulose. Wait until the ethyl cellulose and anhydrous ethanol form a uniform colloid.
[0043] Step 2: Add 40 parts of food additive calcium phosphate to the system in step 1, stirring while adding until the entire system is completely mixed.
[0044] Step 3: Slowly add the mixed materials in the system of step 2 into a beaker filled with water (the amount of water is one-third to two-thirds of the capacity of the vessel), and homogenize with a high-performance homogenizer at a speed of 10,000 rpm. Ethyl cellulose forms a film when it comes into contact with water, and composite material particles are obtained by homogenization.
[0045] Step 4: Place the homogenized material in step 3 on a 60-mesh sieve, wash with water, and sieve out the composite material with a particle size above 60 mesh and the uncompounded calcium phosphate powder.
[0046] Step 5: Collect the cleaned composite material in step 4 and dry it in an oven at 105° C. for about 5 hours.
[0047] Example 3
[0048] The preparation of insoluble adsorption and defluorination composite material particles comprises the following steps:
[0049] Step 1: Weigh ethyl cellulose and anhydrous ethanol in a weight ratio of 18:100, first pour all the anhydrous ethanol into a beaker, then add ethyl cellulose into the beaker, stirring while adding to completely dissolve the ethyl cellulose. Wait until the ethyl cellulose and anhydrous ethanol form a uniform colloid.
[0050] Step 2: Add 50 parts of food additive calcium phosphate to the system in step 1, stirring while adding until the entire system is completely mixed.
[0051] Step 3: Slowly add the mixed materials in the system of step 2 into a beaker filled with water (the amount of water is one-third to two-thirds of the capacity of the vessel), and homogenize with a high-performance homogenizer at a speed of 10,000 rpm. Ethyl cellulose forms a film when it comes into contact with water, and composite material particles are obtained by homogenization.
[0052] Step 4: Place the homogenized material in step 3 on a 60-mesh sieve, wash with water, and sieve out the composite material with a particle size above 60 mesh and the uncompounded calcium phosphate powder.
[0053] Step 5: Collect the cleaned composite material in step 4 and dry it in an oven at 105° C. for about 5 hours.
[0054] like Figure 1 The figure shows a scanning electron microscope image of insoluble adsorption and defluorination composite material particles. It can be seen from the left part of the figure that the adsorption and defluorination composite material particles prepared by the present invention have a rough and porous surface. These structures make the material have a higher specific surface area and pore volume, which is conducive to improving its adsorption performance; the right side of the figure is a scanning electron microscope energy spectrum analysis diagram, which can observe the distribution of calcium elements in the particles, proving that calcium phosphate is more evenly loaded into the ethyl cellulose membrane.
[0055] Example 4
[0056] The preparation of insoluble adsorption and defluorination composite material particles comprises the following steps:
[0057] Step 1: Weigh ethyl cellulose and anhydrous ethanol in a weight ratio of 18:100, first pour all the anhydrous ethanol into a beaker, then add ethyl cellulose into the beaker, stirring while adding to completely dissolve the ethyl cellulose. Wait until the ethyl cellulose and anhydrous ethanol form a uniform colloid.
[0058] Step 2: Add 60 parts of food additive calcium phosphate to the system in step 1, stirring while adding until the entire system is completely mixed.
[0059] Step 3: Slowly add the mixed materials in the system of step 2 into a beaker filled with water (the amount of water is one-third to two-thirds of the capacity of the vessel), and homogenize with a high-performance homogenizer at a speed of 10,000 rpm. Ethyl cellulose forms a film when it comes into contact with water, and composite material particles are obtained by homogenization.
[0060] Step 4: Place the homogenized material in step 3 on a 60-mesh sieve, wash with water, and sieve out the composite material with a particle size above 60 mesh and the uncompounded calcium phosphate powder.
[0061] Step 5: Collect the cleaned composite material in step 4 and dry it in an oven at 105° C. for about 5 hours.
[0062] Example 5
[0063] The preparation of insoluble adsorption and defluorination composite material particles comprises the following steps:
[0064] Step 1: Weigh ethyl cellulose and anhydrous ethanol in a weight ratio of 18:100, first pour all the anhydrous ethanol into a beaker, then add ethyl cellulose into the beaker, stirring while adding to completely dissolve the ethyl cellulose. Wait until the ethyl cellulose and anhydrous ethanol form a uniform colloid.
[0065] Step 2: Add 70 parts of food additive calcium phosphate to the system in step 1, stirring while adding until the entire system is completely mixed.
[0066] Step 3: Slowly add the mixed materials in the system of step 2 into a beaker filled with water (the amount of water is one-third to two-thirds of the capacity of the vessel), and homogenize with a high-performance homogenizer at a speed of 10,000 rpm. Ethyl cellulose forms a film when it comes into contact with water, and composite material particles are obtained by homogenization.
[0067] Step 4: Place the homogenized material in step 3 on a 60-mesh sieve, wash with water, and sieve out the composite material with a particle size above 60 mesh and the uncompounded calcium phosphate powder.
[0068] Step 5: Collect the cleaned composite material in step 4 and dry it in an oven at 105° C. for about 5 hours.
[0069] Effect example
[0070] The insoluble adsorption and defluorination composite material particles of each embodiment were used to carry out the defluorination test. The defluorination rate was calculated according to the following formula:
[0071]
[0072] The results are as follows:
[0073] Table 1: Defluorination effect in tea soup when the dosage of composite material particles is 40g / L (95℃)
[0074]
[0075] It can be seen from the above table that the adsorption defluorination composite material prepared by the present invention has a significant defluorination effect. When the usage of the defluorination composite material particles reaches 40 g / L, when defluoridating tea with a fluorine concentration of 4.76 mg / L, Examples 1-5 all have good defluorination effects.
[0076] Table 2: Defluorination effect in sodium fluoride aqueous solution when the composite material particle dosage is 10g / L (95℃)
[0077]
[0078] It can be seen from the above table that the adsorption and defluorination composite material particles prepared by the present invention have significant defluorination effect. When the usage of the defluorination composite material reaches 10 g / L, when defluoridating a sodium fluoride aqueous solution with a fluorine concentration of 4.86 mg / L, Examples 1-5 all have good defluorination effects.
[0079] After the test, the tea soup and water were filtered separately, and the insoluble adsorption and defluorination composite material particles were collected. After drying, the weight was weighed, which was basically consistent with the weight of the insoluble adsorption and defluorination composite material particles originally added.
[0080] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing insoluble adsorption and defluorination composite material particles, characterized in that: The following steps are involved: 1) dissolving ethyl cellulose in anhydrous ethanol to form a uniform colloid; 2) adding calcium phosphate, a food additive, to the colloid obtained in step 1) under stirring to obtain a uniform mixed material; 3) While the homogenizer is running at high speed, the mixed material obtained in step 2) is slowly added into water, and the ethyl cellulose forms a film when it meets water, and composite material particles are obtained by homogenization; 4) placing the composite material particles obtained in step 3) on a 60-mesh sieve, washing with water, and sieving out composite material particles with a particle size of more than 60 mesh and uncompounded calcium phosphate powder; 5) collecting the sieve material obtained in step 4), drying it, and obtaining the insoluble adsorption and defluorination composite material particles.
2. The method for preparing the insoluble adsorption and defluorination composite material particles according to claim 1, characterized in that: In step 1), the weight ratio of ethyl cellulose to anhydrous ethanol is 6:100 to 18:
100.
3. The method for preparing the insoluble adsorption and defluorination composite material particles according to claim 1, characterized in that: In step 2), the weight ratio of ethyl cellulose to calcium phosphate is 18:10 to 18:
100.
4. The method for preparing the insoluble adsorption and defluorination composite material particles according to claim 1, characterized in that: In step 3), the homogenizing speed is 8000-12000 rpm.
5. The method for preparing the insoluble adsorption and defluorination composite material particles according to any one of claims 1 to 4, characterized in that: In step 5), the drying temperature is 100-110° C. and the drying time is 4-6 hours.
6. Insoluble adsorption and defluorination composite material particles prepared according to the preparation method according to any one of claims 1 to 5.
7. The insoluble adsorption and defluorination composite material particles according to claim 6, characterized in that: The particle size is 0.25mm~2mm.
8. The insoluble adsorption and defluorination composite material particles according to claim 6, characterized in that: Solubility is less than 0.01g / 100g; When the weight ratio of ethyl cellulose to calcium phosphate is 18:50, the adsorption capacity of the composite material particles for fluorine is: 4.90 mg / g at room temperature; and 7.87 mg / g at 95°C.
9. An application of the insoluble adsorption and defluorination composite material particles according to any one of claims 6 to 8, characterized in that: Used to prepare defluorination bags or defluorination agents.
10. A defluorination bag, characterized in that: The invention comprises a sealed bag, and the insoluble fluorine-removing adsorption composite material particles as claimed in any one of claims 6 to 8 filled in the bag.
Citation Information
Patent Citations
Low-fluorine brick tea production process employing microorganism preparation treatment
CN101427716A
Medicament method brick-tea defluorination device
CN101507457A
Manufacturing process for dual-calcium-fortified low-fluorine brick tea
CN103734365A
Low-fluorine brick tea and production process
CN1085050C
Preparing method of low-fluorine brick tea
CN110150411A